In-Peat Geomechanical Monitoring Method under Actual Road Embankment - Alsidqi Hasan; Jeffery Tay; Jye Lee (Himpunan Ahli Teknik Tanah Indonesia, 2023)
This paper presents an ongoing ‘in-peat’ geomechanical monitoring exercise under an actual road embankment that is being constructed in Sarawak State of Malaysia. The road embankment will serve as part of 236km second trunk road, which is expected to be completed in 2 years. It measures about 34m wide and 3m high, overlies 5m thick of peat and a soft clay. In-peat monitoring method uses a technique that can monitor the vertical stress, the horizontal stress, the pore water pressure, and the settlement from within the peat layer. This complete set of data are valuable to back analyze the phenomena takes place during and post construction, using the state-of-the-art concept in soil mechanics. Detail site information, installation method and preliminary data are discussed. The installation exercise has been finished and the in-peat monitoring has been started. A professional service was appointed to install and monitor the sensors, which is supervised by the academic and the department of public works. The in-peat monitoring is a critical milestone to better understand the geomechanical behavior of peat under actual road embankment and to verify the current peat conceptual model.